A new dynamic bandwidth allocation algorithm for fiber wireless network - Radzi N.A.M.; Din N.M.; Rawi N.I.M.; Abdullah F.; Ismail A.; Al-Mansoori M.H. (Institute of Electrical and Electronics Engineers Inc., 2023)
Algorithms; Bandwidth; Carrier communication; Carrier sense multiple access; Frequency allocation; Passive optical networks; Wi-Fi; Band-width utilization; Carrier sense multiple access with collision avoidances; CSMA/CA; delay; Dynamic bandwidth allocation; Dynamic bandwidth allocation algorithms; Fiber-wireless; Gigabit passive optical network; Time division multiple access